Agreement between two large pan-cancer CRISPR-Cas9 gene dependency data sets - Joshua M. Dempster (Nature Portfolio, 2019)
Integrating independent large-scale pharmacogenomic screens can enable unprecedented characterization of genetic vulnerabilities in cancers. Here, the authors show that the two largest independent CRISPR-Cas9 gene-dependency screens are concordant, paving the way for joint analysis of the data sets.